2012
DOI: 10.1080/00224499.2011.637247
|View full text |Cite
|
Sign up to set email alerts
|

Victimization Experiences of Lesbian, Gay, and Bisexual Individuals: A Meta-Analysis

Abstract: This meta-analysis quantitatively compiled the results of studies from 1992 to 2009 to determine the prevalence and types of victimization experienced by lesbian, gay, and bisexual (LGB) individuals. Based on the results of three searches, 386 studies were retrieved and coded. Comparisons were made across all LGB individuals (138 studies), between LGB and heterosexual individuals (65 studies), and between LGB females and males (53 studies), with over 500,000 participants. Multiple types of victimization were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
339
3
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(376 citation statements)
references
References 68 publications
24
339
3
10
Order By: Relevance
“…Reviews reveal higher probabilities of suffering bullying and other violent acts in life among LGB (Fedewa & Ahn, 2011;Katz-Wise & Hyde, 2012). Other frequent risk mechanisms deriving from social prejudice are expected rejection, hiding one's sexual orientation and internalized homophobia (Meyer, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Reviews reveal higher probabilities of suffering bullying and other violent acts in life among LGB (Fedewa & Ahn, 2011;Katz-Wise & Hyde, 2012). Other frequent risk mechanisms deriving from social prejudice are expected rejection, hiding one's sexual orientation and internalized homophobia (Meyer, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Third, a large body of research has documented greater levels of lifetime victimization 47 among SMW and the influence on sexual risk behaviors, [48][49][50] which may lead to unintended pregnancy. In fact, research has shown that bisexual and lesbian identified adolescent girls have a greater risk of reporting teen pregnancy than heterosexual girls.…”
Section: Introductionmentioning
confidence: 99%
“…A part of the differences that have been found regarding mental health may be explained by direct experiences of homophobic related violence. In fact, GLB youths suffer more lifetime victimization than their heterosexual counterparts, and are more likely to be victims of bullying at school (Fedewa & Ahn, 2011;Katz-Wise & Hyde, 2012). D'Augelli (2002), in a study of GLB North American youths, found that 81% of participants reported having been verbally insulted and 38% were physically threatened during their lifetimes.…”
mentioning
confidence: 99%